"Tankrabatt" und "Freiheitsenergie". Wie der Blog "neusprech.org" politische Euphemismen entlarvt - Tophinke, Doris (Zwischen Fake und Fakt)

Annotation uncertainty in the context of grammatical change - Merten, Marie-Luis; Wever, Marcel; Tophinke, Doris; Geierhos, Michaela; Hüllermeier, Eyke (International Journal of Corpus Linguistics)

Digital Democracy and the Digital Public Sphere - Fuchs, Christian

Pop(musik)journalismen zwischen Printmagazin-Krise und postdigitaler Realität – Forschungsüberblick und multiperspektivische Thesen - Godlewsky, Tanja; Jacke, Christoph; Roenneke, Stefanie; Venker, Thomas (Musik und Internet. Aktuelle Phänomene populärer Kulturen)
Dieser Beitrag bietet verschiedene professionelle Perspektiven auf den popmusikalischen Kommunikationsprozesses innerhalb postdigitaler Popmusikjournalismuskulturen. Neben einer wissenschaftlichen Rahmung, Übersicht und Strukturierung des Untersuchungsfelds und des Forschungsstands versammelt der Beitrag multiperspektivische Thesen, die journalistische Praktiken und ihre Reflexionen von Produktion über Distribution und Rezeption/Nutzung bis zur Weiterverarbeitung inklusive Archivierung/Institutionalisierung/Musealisierung aufgreifen und herausstellen. Die aufgestellten Thesen gelten als Aufschlag für die zukünftige Analyse des so fundamentalen und doch auch immer wieder übersehenen Berufsfeldes und seiner Rezeption zwischen Faszination und Exploitation.

„Die Prüfungen werden mich sicherlich nicht zu einer besseren Lehrkraft machen.“ Wie beurteilen Studierende Prüfungen und Feedback im Lehramtsstudium? - Vogelsang, Christoph; Janzen, Thomas; Meier, Jana; Wotschel, Philipp

Als Lehrkraft gut beraten? Entwicklung und Erprobung eines handlungsnahen Prüfungsformates zur Erfassung von Beratungskompetenz von Lehramtsstudierenden - Wotschel, Philipp; Vogelsang, Christoph; Janzen, Thomas; Meier, Jana

My first contact with the Foodsharing Initiative - Vochatzer, Stefanie (Creative Approaches to Climate and Peace Education. An Educationr’s Guide to Using Storytelling and Art)

»In der Art von Inschriften«. Emblematische Inschriftendichtung als Darstellungsprinzip von Ferdinand von Fürstenbergs Monumenta Paderbornensia (1669 und 1672) - Süßmann, Johannes (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornensia des Ferdinand von Fürstenberg)

Perceptions of inclusion in students with diagnosed behavioural, emotional and social difficulties (BESD) displaying internalising and externalising behaviour in inclusive and special education - Zdoupas, Philippos; Laubenstein, Désirée (European Journal of Special Needs Education (Latest Articles))

Entwicklungszielgespräche in der Sekundarstufe I - Systemisches Coaching mit Schüler:innen nach dem GROW-Modell - Zdoupas, Philippos; Lara, Kuhlhoff; Martin, Grust; Jaekel, Anne-Marie; Jan, Ehlert

Life Storying in Oral History: Fictional Contamination and Literary Complexity - Mildorf, Jarmila

Das Aufbegehren der Eroberten. Absichten, Formen und Deutungen im europäischen Mittelalter (8. bis 14. Jahrhundert) - Kamp, Hermann (Eroberte im Mittelalter. Umbruchssituationen erleben, bewältigen, gestalten)

Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Counselling competence of student teachers – development of an action-oriented assessment format. - Wotschel, Philipp; Vogelsang, Christoph; Meier, Jana; Janzen, Thomas

Assessing pre-service EFL teachers’ feedback performance in role-play-based simulations. - Janzen, Thomas; Wotschel, Philipp; Meier, Jana; Vogelsang, Christoph

Acceptance of simulation-based assessment formats in teacher education. - Vogelsang, Christoph; Meier, Jana; Janzen, Thomas; Wotschel, Philipp

Parallele Universen des Wissenschaftsmanagements? Ein Vergleich des Wissenschaftsmanagements an Hochschulen und außeruniversitären Forschungseinrichtungen in Deutschland. - Schneider, Sebastian; Mauermeister, Sylvi; Henke, Justus; Aust, Robert (Hochschulmanagement. Zeitschrift für die Leitung, Entwicklung und Selbstverwaltung von Hochschulen und Wissenschaftseinrichtungen.)
The development of good conditions for research is an essential task of research institutions, which in practice is nowadays mostly performed by science managers. Research in the field of science management in Germany mainly refers to developments at universities, whereas little is known about the situation at so called non-university research organisations. At the same time, there are hardly any statistics on the size of the science management in Germa-ny. In order to take first steps towards exploring these parallel universes, this article presents a comparative mapping of science management at universities and non-university research organisations for Germany by drawing on a special analysis of the German Federal Statistical Office and an online survey.

Citizen Science: Laien-Partizipation an Forschung - Göbel, Claudia; Henke, Justus; Mauermeister, Sylvi; Pasternack, Peer (Wissenschaftskommunikation, neu sortiert.)

Gesellschaftlich-demokratische Teilhabe: trotz hochschulischer oder durch hochschulische Bildung? - de Angelis, Moira; Harles, Dorothea; Mauermeister, Sylvi; Aust, Robert (Das Hochschulwesen)

Editorial - Schönhärl, Korinna; Schotters, Frederike; Thiemeyer, Guido (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Ver- gangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischen- menschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuch en Gelddis- kurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Internationale Finanzkontrollen: Griechenland unter internationaler Kuratel im 19. und 21. Jahrhundert - Schönhärl, Korinna (Schulden machen: Praktiken der Staatsverschuldung im langen 20. Jahrhundert)
Ob als Effekt staatlicher Hilfspakete, als kontroverses Thema des EU-Haushalts oder als mögliche Ursache der rasant steigenden Inflation – in einer Welt im Krisenmodus ist das Problem der Staatsverschuldung aktuell wie selten zuvor. Wie und von wem aber werden Staatsschulden tatsächlich »gemacht«? Und wie stellt sich dies in der historischen Perspektive dar? Die Essays dieses Bandes machen das abstrakte Phänomen der öffentlichen Verschuldung und die verborgenen Prozesse hinter den Schuldenquoten zugänglich. Prägende Praktiken der Staatsverschuldung verdeutlichen die Beiträge anhand von fünf Kategorien: den beteiligten Akteuren, den konkreten Artefakten, den politischen Debatten, den globalen Relationen sowie der Zeitlichkeit der Verschuldung der öffentlichen Haushalte.
Keywords: Financial History; Public Debt; Economic History

Reden über Geld (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Vergangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischenmenschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuchen Gelddiskurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Contrastiveness in the context of action demonstration: an eye-tracking study on its effects on action perception and action recall - Singh, Amit; Rohlfing, Katharina J. (Proceedings of the Annual Meeting of the Cognitive Science Society 45 (45))
The study investigates two different ways of guiding the addressee of an explanation - an explainee, through action demonstration: contrastive and non-contrastive. Their effect was tested on attention to specific action elements (goal) as well as on event memory. In an eye-tracking experiment, participants were shown different motion videos that were either contrastive or non-contrastive with respect to the segments of movement presentation. Given that everyday action demonstration is often multimodal, the stimuli were created with re- spect to their visual and verbal presentation. For visual presentation, a video combined two movements in a contrastive (e.g., Up-motion following a Down-motion) or non-contrastive way (e.g., two Up-motions following each other). For verbal presentation, each video was combined with a sequence of instruction descriptions in the form of negative (i.e., contrastive) or assertive (i.e., non-contrastive) guidance. It was found that a) attention to the event goal increased for this condition in the later time window, and b) participants’ recall of the event was facilitated when a visually contrastive motion was combined with a verbal contrast.
Keywords: Attention; negation; contrastive guidance; eye-movements; action understanding; event representation

Zur Kritik der Politischen Ökonomie des Digitalen Kapitalismus: Die Aktualität von Manfred Knoches Beitrag zur Kritik der Politischen Ökonomie der Medien und der Kommunikation - Fuchs, Christian (Eigentum, Medien, Öffentlichkeit: Verhandlungen des Netzwerks Kritische Kommunikationswissenschaft)

The Problems of Base/Superstructure and Ideology in the Works of Stuart Hall, Georg Lukács, and Raymond Williams - Fuchs, Christian (The Communication Review.)
We live in times of deep crisis. General crises of society often are accompanied by ideological struggles. Given this context, it is important that social theory reinvigorates the analysis of ideology. For doing so, it makes sense to engage with classical theories of ideology. This paper contributes to this task. It asks: How are the economic and the non-economic related? What is ideology? This article deals with the base/superstructure problem and the problem of ideology via an engagement with selected aspects of Stuart Hall’s, Georg Lukács’s and Raymond Williams’s works. The commonality of Hall’s, Lukács’s and Williams’s thoughts that makes a joint engagement with their works feasible is that they all three dealt with aspects of culture from a critical theory perspective and are in one way or another representatives of Cultural Marxism. While Lukács’s works and Cultural Studies are often presented as conflicting approaches, this paper shows that concerning the question of how the economic and the non-economic are related and how we can think of ideology, the approaches of Lukács, Williams, and Hall complement each other, which allows critical theories of culture to draw on all three approaches and to combine elements from them in a synergistic manner. There are parallels between Williams’, Hall’s, and Lukács’s solutions to the base/superstructure problem. Williams argues that the economic exerts pressures on and sets limits to the non-economic. Hall writes that the economic determines the non-economic in the first instance. Lukács argues that the economic circumscribes subjectivity and the non-economic.
Keywords: base and superstructure; culture; economy and culture; Georg Lukács; ideology; Raymond Williams; Stuart Hall

Digitale Desökonomie: Unproduktivität, Trägheit und Exzess im digitalen Milieu - Althoff, Sebastian

Food - Media - Senses

Dialogical Functions of You-Narration in Auto/Biography: Anne Harich’s “Wenn ich das gewußt hätte…”: Erinnerungen an Wolfgang Harich (2007) - Mildorf, Jarmila (Zagadnienia Rodzajów Literackich)

The Literary in Narrating Dramatic Life Experiences - Hatavara, Mari; Hyvärinen, Matti; Mildorf, Jarmila (The Routledge Companion to Literary Media)

Poeticity and Parody: The Literary Interview on Radio and Podcast - Mildorf, Jarmila (The Routledge Companion to Literary Media)

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.

Fünf Thesen zur Untersuchung des Textsortenwandels - Schuster, Britt-Marie; Haaf, Susanne (Historische Textmuster im Wandel. Neue Wege zu Ihrer Erschließung)

Fragen stellen in Pressetextsorten - Schuster, Britt-Marie; Thielert, Frauke; Haaf, Susanne (Historische Textmuster im Wandel. Neue Wege zu ihrer Erschließung)

»Das dankst du deinem Führer« – Adressierungspraktiken in der Widerstandskommunikation gegen den Nationalsozialismus - Schuster, Britt-Marie (Kommunikative Praktiken im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

Widerstandshandeln. Sprachliche Praktiken des Sich-Widersetzens zwischen 1933 und 1945

Tax Morale and the Church: How Catholic Clergies Adapted Norms of Paying Taxes to Secular Institutions (1940s–1950s) - Schönhärl, Korinna (Reassessing the Moral Economy Religion and Economic Ethics from Ancient Greece to the 20th Century)
Paying taxes is a field of economic activity that has always been highly morally charged: the question of who pays how much or can avoid or evade the prescribed payments is always closely related to debate about a fair societal distribution of burdens. In the process of moralisation, therefore, faith communities such as the Catholic Church also repeatedly seized the floor to propagate certain norms. The article examines the contributions of theologians from Spain, the USA and West Germany in the 1940s and 1950s. It concludes that the norms of taxation they propagated differed greatly depending on the institutional and economic frameworks within which they operated. The analysis proves taxation to be a field of economic action and societal dispute where economics and morality are indissolubly interconnected.
Keywords: Tax history; religious history: financial history; catholic church; history of economic thought

Bildungsforschung – Erziehungswissenschaftliche Perspektiven

Vergleichskonstruktionen im Mittelniederdeutschen - Wallmeier, Nadine; Wich-Reif, Claudia (Historische (Morpho-)Syntax des Deutschen)

Sarah Ihnen (2000): Relativsätze im Mittelniederdeutschen. Korpuslinguistische Untersuchungen zu Struktur und Gebrauch. - Wallmeier, Nadine (Linguistische Berichte)

Regierende Herrscherwitwen und die Angst vor Fremdherrschaft. Zum Verhältnis von Dynastie und Geschlecht - Foerster, Anne (Regentinnen und andere Stellvertreterfiguren Vom 10. bis zum 15. Jahrhundert)

Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

Review on: Christos Tsakas: Post-war Greco-German Relations, 1953-1981. Economic Development, Business Interests and European Integration, Basingstoke 2022. - Schönhärl, Korinna (Sehepunkte)

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Editorial. - Jacke, Christoph; Autsch, Sabine; Pickartz, Tim (Impulse. Texte und Bilder zur Kunstvermittlung.)

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, A.; Singh, Amit; Banh, Ngoc Chi; Richter, B.; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, B. (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: HRI; XAI; negation; understanding; explaining; touch interaction; gesture

When Did Europe Become Identified With Christianity? The Revolutionary Origins of an All Too Common Slogan - Süßmann, Johannes (Beyond Binaries. Religious Diversity in Europe)

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Conjunctive and additive group work reduce academic procrastination: insights from a vignette study - Koppenborg, Markus; Klingsieck, Katrin B.; Hüffmeier, Joachim (Current Psychology)
Abstract Group work can increase individual effort, performance, and positive affect, if group members perceive their own contribution as indispensable for the group product. A vignette methodology was applied to investigate whether group work may also reduce procrastination. The vignettes described a typical academic assignment, while varying the task structure (individual work vs. conjunctive group work vs. additive group work) and group member ability (high vs. low). For each vignette, student participants ( N = 443) provided ratings on their perceived indispensability, procrastination of the assignment, and affect. When group member ability was high, procrastination was lower in additive group work as compared to individual work. When group member ability was low, procrastination was lower in conjunctive group work as compared to both individual work and additive group work. As predicted, perceived indispensability mediated the difference in procrastination between conjunctive and additive group work. Moderation analyses further revealed that the effects were more pronounced for high trait procrastinators. Further, both types of group work led to increases in task-related positive affect as compared to individual work. By demonstrating the relevance of group work as a social factor, the results should be useful for the extension of existing programs targeting procrastination, and may inspire measures for preventing procrastination by changes in the study environment.
Keywords: General Psychology

GEProS - Entwicklung und Evaluation einer digitalen Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden - Grotegut, Lea
Um Schüler*innenmerkmale korrekt zu beurteilen benötigen Lehrkräfte diagnostische Kompetenz. Insbesondere die genaue Einschätzung nicht-kognitiver Merkmale von Schüler*innen fällt Lehrkräften eher schwer. Dazu zählen auch mögliche Anzeichen für Lern- und Verhaltensauffälligkeiten. Maßnahmen zur Förderung diagnostischer Kompetenz fokussieren bisher größtenteils die Diagnostik fachspezifischer, situativer Urteilsgegenstände, wie Fehlkonzepte im Mathematikunterricht. Systematisch evaluierte Fördermaßnahmen, die das Erkennen und Beurteilen von Lern- und Verhaltensauffälligkeiten bei Schüler*innen fokussieren, existieren bisher nicht.Aus diesem Anlass wurde die digitale, problemorientierte Simulation GEProS zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden entwickelt und systematisch in drei längsschnittlichen, (quasi-)experimentellen Kontrollgruppenstudien evaluiert. Die Ergebnisse zeigen, dass die GEProS einen Mehrwert für die Förderung diagnostischer Kompetenz insbesondere im Bereich selbstbestimmter Motivation bieten kann. Ein integriertes Quiz mit Feedback kann mittels testing effect darüber hinaus der Erwerb deklarativ-konzeptionellen Wissens als zentrale Disposition diagnostischer Kompetenz in GEProS unterstützen. Die Ergebnisse tragen durch das entwickelte Integrative Modell diagnostischer Kompetenz zur Theoriebildung sowie zur Forschung und Entwicklung im Bereich der Förderung diagnostischer Kompetenz bei, indem eine Maßnahme zur Förderung diagnostischer Kompetenz für einen fächerübergreifenden, zeitlich stabilen Urteilsgegenstand systematisch evaluiert wurde. Durch die Ableitung und Berücksichtigung wesentlicher Merkmale digitaler Simulationen trägt diese Arbeit außerdem zur theoretischen Fundierung digitaler Simulationen bei.

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science